“Candidatus Hepatoplasma crinochetorum,” a New, Stalk-Forming Lineage of Mollicutes Colonizing the Midgut Glands of a Terrestrial Isopod - Wang, Yongjie (American Society for Microbiology, 2004)
Uncultivated bacteria that densely colonize the midgut glands (hepatopancreas) of the terrestrial isopod Porcellio scaber (Crustacea: Isopoda) were identified by cloning and sequencing of their 16S rRNA genes. Phylogenetic analysis revealed that these symbionts represent a novel lineage of the Mollicutes and are only distantly related (<82% sequence identity) to members of the Mycoplasmatales and Entomoplasmatales. Fluorescence in situ hybridization with a specific oligonucleotide probe confirmed that the amplified 16S rRNA gene sequences indeed originated from a homogeneous population of symbionts intimately associated with the epithelial surface of the hepatopancreas. The same probe also detected morphotypically identical symbionts in other crinochete isopods. Scanning and transmission electron microscopy revealed uniform spherical bacterial cells without a cell wall, sometimes interacting with the microvilli of the brush border by means of stalk-like cytoplasmic appendages, which also appeared to be involved in cell division through budding. Based on the isolated phylogenetic position and unique cytological properties, the provisional name “Candidatus Hepatoplasma crinochetorum” is proposed for this new taxon of Mollicutes colonizing the hepatopancreas of P. scaber.